Menin‐regulated Pbk controls high fat diet‐induced compensatory beta cell proliferation - Jian Ma; Bowen Xing; Yan Cao; Xin He; Kate E Bennett; Chao Tong; Chiying An; Taylor Hojnacki; Zijie Feng; Sunbin Deng; Sunbin Ling; Gengchen Xie; et al. (EMBO Molecular Medicine)
Abstract Pancreatic beta cells undergo compensatory proliferation in the early phase of type 2 diabetes. While pathways such as FoxM1 are involved in regulating compensatory beta cell proliferation, given the lack of therapeutics effectively targeting beta cell proliferation, other targetable pathways need to be identified. Herein, we show that Pbk, a serine/threonine protein kinase, is essential for high fat diet (HFD)‐induced beta cell proliferation in vivo using a Pbk kinase deficiency knock‐in mouse model. Mechanistically, JunD recruits menin and HDAC3 complex to the Pbk promoter to reduce histone H3 acetylation, leading to epigenetic repression of Pbk expression. Moreover, menin inhibitor (MI) disrupts the menin–JunD interaction and augments Pbk transcription. Importantly, MI administration increases beta cell proliferation, ameliorating hyperglycemia, and impaired glucose tolerance (IGT) in HFD‐induced diabetic mice. Notably, Pbk is required for the MI‐induced beta cell proliferation and improvement of IGT. Together, these results demonstrate the repressive role of the menin/JunD/Pbk axis in regulating HFD‐induced compensatory beta cell proliferation and pharmacologically regulating this axis may serve as a novel strategy for type 2 diabetes therapy.